2016
DOI: 10.1007/s10151-016-1498-3
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and colorectal cancer prognosis: a systematic review and meta-analysis

Abstract: Colorectal cancer is one of the most common cancers worldwide. However, it is unclear what influence body mass index (BMI) has on colorectal cancer prognosis. We conducted a systematic review and meta-analysis of observational studies to examine the association of BMI with colorectal cancer outcomes. We searched MEDLINE and EMBASE databases from inception to February 2015 and references of identified articles. We selected observational studies that reported all-cause mortality, colorectal cancer-specific morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 64 publications
(74 reference statements)
3
80
1
Order By: Relevance
“…Recent meta-analysis or systematic review papers revealed that uncontrolled diabetes, 14 obesity and underweight, 15 smoking, 16 western dietary pattern, 4 and physical inactivity 4 were correlated with poor overall survival. We found that underweight, smoking, and physically inactivity were all associated with all-cause mortality risk in line with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analysis or systematic review papers revealed that uncontrolled diabetes, 14 obesity and underweight, 15 smoking, 16 western dietary pattern, 4 and physical inactivity 4 were correlated with poor overall survival. We found that underweight, smoking, and physically inactivity were all associated with all-cause mortality risk in line with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…have recently conducted a meta‐analysis on the effects of BMI following the diagnosis of colorectal cancer. They have reported that a low BMI is associated with increased all‐cause mortality and cancer‐specific mortality 72. This suggests that underweight patients might have lower nutritional statuses and lower body muscle content than individuals with normal bodyweight.…”
Section: Resultsmentioning
confidence: 99%
“…Features of the metabolic syndrome, such as diabetes and obesity, have been associated with both increased risk of cancer development and cancer‐related mortality regarding both gastrointestinal (colorectal, oesophagus, stomach and pancreas) and extra‐intestinal (kidney and breast) malignancies . The increased oncologic risk would be because of a number of molecular mechanisms (insulin resistance, chronic inflammation, reduced apoptosis and imbalance of gut microbiota) that initiate and fuel carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%